Can you patent an industry standard?. - Frank, S.J (IEEE spectrum)
We live in an age of industry standards. Particularly in the various fields of electronics, standards developed by volunteers are becoming so numerous and so detailed that it's difficult even to be aware of them all, at least outside one's own engineering specialty. In this paper, the author examines whether one can patent an industry standard. He concludes that one can, but that the licensing process requires as much transparency as developing the standard does in the first place